Electrospun Poly-L-Lactic Acid Scaffolds Surface-Modified via Reactive Magnetron Sputtering Using Different Mixing Ratios of Nitrogen and Xenon - Marjin (Maryin) P. V. Pavel Vladimirovich; Chan Tuan Khoang; Frolova A. A. Anastasiya Aleksandrovna; Buldakov M. A. Mikhail Aleksandrovich; Choynzonov E. L. Evgeny Lkhamatsyrenovich; Kozelskaya A. I. Anna Ivanovna; Rutkowski S. Sven; Tverdokhlebov S. I. Sergei Ivanovich (2023, 2023)
Title screen